KOMODIFIKASI NILAI ISLAM DALAM FASHION MUSLIM DI INSTAGRAM - Khairul Syafuddin; Ni’amatul Mahfiroh (Profetika: Jurnal Studi Islam, 2020)
One effect of the development of internet technology is the birth of social media. Instagram is a social media that is currently used by more than 61 million people in Indonesia. The number shows that Instagram has become an effective tool for an industry in the context of political economy practices, one of which is in the Muslim fashion industry. One of the Muslim fashion industries engaged in the digital world is santun.inv. This account has compared him to being a producer of the hijrah shirt. Based on its branding and products sold through its Instagram account, it can be seen in this account that has carried out the commodification of Islamic values through commodity tools. That way it can be seen, now the value of Islam can not only be operated at the level of scientific review and da’wah. But the function has shifted to become an economic tool.